2017
DOI: 10.3390/molecules22030445
|View full text |Cite
|
Sign up to set email alerts
|

A Model Study of the Photochemical Fate of As(III) in Paddy-Water

Abstract: The APEX (Aqueous Photochemistry of Environmentally-occurring Xenobiotics) software previously developed by one of us was used to model the photochemistry of As(III) in paddy-field water, allowing a comparison with biotic processes. The model included key paddy-water variables, such as the shielding effect of the rice canopy on incident sunlight and its monthly variations, water pH, and the photochemical parameters of the chromophoric dissolved organic matter (CDOM) occurring in paddy fields. The half-life tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Indeed, we have recently shown that May (referred to temperate areas of the northern hemisphere) is by far the most favorable month for photochemistry in paddies. Plant shadowing plays an important role in inhibiting photoreactions from mid-June onward, despite the usually higher sunlight irradiance compared to May . DCA may be generated upon microbial degradation of the postemergence herbicide propanil, , which is usually sprayed in the second half of May and has a short (day-range) lifetime .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have recently shown that May (referred to temperate areas of the northern hemisphere) is by far the most favorable month for photochemistry in paddies. Plant shadowing plays an important role in inhibiting photoreactions from mid-June onward, despite the usually higher sunlight irradiance compared to May . DCA may be generated upon microbial degradation of the postemergence herbicide propanil, , which is usually sprayed in the second half of May and has a short (day-range) lifetime .…”
Section: Resultsmentioning
confidence: 99%